Fibrous cellulose-containing fluid dispersion and production method thereof
A fibrous cellulose dispersion with controlled viscosity and ionic substituents addresses the issue of coating suitability in paints by maintaining stability and preventing issues like dripping and sedimentation, enhancing the paint's performance.
Patent Information
- Application Number
- JP2024157353
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-04-22
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-04-22
AI Technical Summary
Conventional cellulose nanofibers in paints suffer from a lack of attention to viscosity changes due to shear, leading to decreased coating suitability and stability.
A fibrous cellulose-containing dispersion with specific properties, including a fiber width of 1000 nm or less, ionic substituents, and controlled viscosity, is added to paints to improve dispersion stability and coating suitability.
The dispersion maintains excellent stability and coating suitability by controlling viscosity changes, preventing dripping and sedimentation, and enhancing the smoothness and design of the coating film.
Smart Images

Figure 2024178228000008 
Figure 2024178228000009 
Figure 2024178228000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fibrous cellulose-containing dispersion and a method for producing the same. [Background technology]
[0002] Cellulose fibers have been widely used in clothing, absorbent articles, paper products, etc. As cellulose fibers, in addition to fibrous cellulose with a fiber diameter of 10 μm to 50 μm, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. Fine fibrous cellulose has attracted attention as a new material and has a wide range of applications.
[0003] For example, fine fibrous cellulose may be used as an additive for paints. In this case, the fine fibrous cellulose may function as a viscosity modifier in paints. For example, Patent Document 1 discloses a glittering pigment dispersion containing water, a viscosity modifier (A) and a scaly glittering pigment (B). Patent Document 2 discloses a glittering pigment dispersion containing water, a scaly aluminum pigment and a cellulose-based viscosity modifier. Patent Documents 1 and 2 discuss the use of cellulose nanofibers as a viscosity modifier. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 012014 [Patent Document 2] International Publication No. 2017 / 175468 Summary of the Invention [Problem to be solved by the invention]
[0005] Conventionally, cellulose nanofibers have been used in paints to improve the dispersibility of pigments, etc. However, no attention has been paid to the problem of reduced coatability caused by viscosity changes (thixotropy) caused by applying shear before coating, and there has been room for improvement in coatability.
[0006] Therefore, in order to solve such problems of the conventional technology, the present inventors have carried out research with the aim of providing a dispersion containing fine fibrous cellulose that can exhibit excellent dispersibility stability and excellent coating suitability when added to a coating material. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the inventors have found that when a specified fine fibrous cellulose is dispersed in water to prepare a fibrous cellulose-containing dispersion, the dispersion has a specified viscosity, and by adding the fine fibrous cellulose-containing dispersion to a paint, it is possible to improve the coating suitability of the paint while maintaining excellent dispersibility stability. Specifically, the present invention has the following configuration.
[0008] [1] A dispersion containing fibrous cellulose, the fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent, A fibrous cellulose-containing dispersion, in which the amount of ionic substituents in the fibrous cellulose is 0.10 mmol / g or more and 1.50 mmol / g or less, the degree of polymerization of the fibrous cellulose is 150 or more and 515 or less, the viscosity at 3 rpm using a B-type viscometer is 40,000 mPa·s or more and 800,000 mPa·s or less, and the concentration of the fibrous cellulose in the dispersion is 1.5 mass% or more and less than 5 mass%. [2] The fibrous cellulose-containing dispersion according to [1], wherein the ionic substituent is a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group. [3] The fibrous cellulosic cellulose-containing dispersion according to [1] or [2], having a viscosity of 300,000 mPa or more and 5,000,000 mPa or less at 0.3 rpm using a Brookfield viscometer. [4] The fibrous cellulose-containing dispersion according to any one of [1] to [3], wherein the ratio of the viscosity at 0.3 rpm using a B-type viscometer to the viscosity at 3 rpm using a B-type viscometer (viscosity at 0.3 rpm / viscosity at 3 rpm) is 5.00 or more and 7.40 or less. [5] Rheometer shear rate 1 sec -1 The fibrous cellulose-containing dispersion according to any one of [1] to [4], wherein the viscosity under the above conditions is 30 Pa·s or more and 400 Pa·s or less. [6] Rheometer shear rate 1000 sec -1 The fibrous cellulose-containing dispersion according to any one of [1] to [5], wherein the viscosity under the above conditions is 0.02 Pa·s or more and 1.00 Pa·s or less. [7] Rheometer shear rate: 1000 sec -1 Viscosity at the shear rate of 1sec in the rheometer -1 The viscosity ratio under the condition of (shear rate 1sec -1 Viscosity under the condition of shear rate 1000sec -1 The fibrous cellulose-containing dispersion according to any one of [1] to [6], wherein the viscosity under the above conditions is 200 or more and 1,000 or less. [8] The fibrous cellulose-containing dispersion according to any one of [1] to [7], wherein when the fibrous cellulose-containing dispersion is diluted with a dispersion solvent containing water and isopropol to obtain a dispersion having a water to isopropanol mass ratio of 7:3 and a viscosity of 2500 mPa s at 23°C, and the diluted dispersion is stirred under the following stirring conditions, the viscosity change rate calculated by the following formula is within ±50%; Viscosity change rate (%) = (viscosity after stirring - viscosity before stirring) / viscosity before stirring x 100 (Mixing conditions) A dispersion with a viscosity of 2500 mPa s at 23°C is poured into a cylindrical container with a diameter of 10 cm to a height of 5 cm. It is stirred for 24 hours at 23°C using an elliptical stirrer that is 5 cm long, 2 cm wide at the centre and 1 cm wide at the ends, while maintaining a 2 cm depression in the centre of the liquid surface. [9] The fibrous cellulose-containing dispersion according to any one of [1] to [8], wherein when the fibrous cellulose-containing dispersion is diluted with water to give a fibrous cellulose content of 0.4 mass%, the viscosity of the diluted dispersion at 23°C is 20 mPa s or more and 4,700 mPa s or less.
[10] The fibrous cellulose-containing dispersion according to any one of [1] to [9], wherein when the fibrous cellulose-containing dispersion is diluted with water to give an aqueous dispersion having a fibrous cellulose content of 0.2 mass%, the haze of the diluted dispersion is 20% or less.
[11] The fibrous cellulose-containing dispersion according to any one of [1] to
[10] , which is for use in a paint.
[12] A method for producing a fibrous cellulose-containing dispersion liquid, comprising the steps of: subjecting cellulose fibers having an ionic substituent of 0.10 mmol / g or more and 1.50 mmol / g or less to a defibration treatment to obtain fibrous cellulose having a fiber width of 1000 nm or less; and subjecting the fibrous cellulose to a thixotropy reduction treatment, wherein the thixotropy reduction treatment step is a step of reducing the degree of polymerization of the fibrous cellulose to 150 or more and 515 or less. Effect of the Invention
[0009] According to the present invention, it is possible to obtain a fine fibrous cellulose-containing dispersion liquid which, when added to a paint, exhibits excellent dispersion stability for pigments and the like and excellent suitability for coating. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. [Diagram 2]FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having a carboxy group and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description of the components may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.
[0012] (Fine fibrous cellulose-containing dispersion) This embodiment relates to a dispersion containing fibrous cellulose having a fiber width of 1000 nm or less and having an ionic substituent. The amount of ionic substituent in the fibrous cellulose in this embodiment is 0.10 mmol / g or more and 1.50 mmol / g or less, and the degree of polymerization of the fibrous cellulose is 150 or more and 515 or less. In this specification, fibrous cellulose having a fiber width of 1000 nm or less is also referred to as fine fibrous cellulose. Here, the fibrous cellulose-containing dispersion of this embodiment has a fibrous cellulose concentration in the dispersion of 1.5 mass% or more and less than 5 mass%, and a viscosity at 3 rpm using a Brookfield viscosity system of 40,000 mPa·s or more and 800,000 mPa·s or less.
[0013] By adding the fibrous cellulose-containing dispersion liquid of this embodiment to a paint, it is possible to impart to the paint excellent dispersion stability for particles such as pigments and excellent coatability. In general, by adding a dispersion containing fine fibrous cellulose having a fiber width of 1000 nm or less to a paint, etc., the viscosity of the paint can be improved and the dispersibility of particles in the paint can be improved. However, when a paint containing a dispersion containing fine fibrous cellulose, which has high thixotropy, is subjected to a relatively high shear force, the viscosity is excessively reduced, causing problems such as dripping and settling of additives such as pigments. The dispersion in which the fine fibrous cellulose of this embodiment is dispersed has thixotropy controlled within an appropriate range, and can exhibit excellent coating suitability. For example, even when the paint containing the fine fibrous cellulose of this embodiment is stored or transported, the viscosity change of the paint is suppressed within an appropriate range, so that dripping during coating is suppressed and the sedimentation of additives such as pigments can be suppressed. In addition, even when the paint containing the fine fibrous cellulose dispersion of this embodiment is stirred for a long time and a relatively strong shear is applied to the paint, dripping caused by the decrease in viscosity of the paint and the sedimentation of additives such as pigments can be effectively suppressed. Furthermore, the fine fibrous cellulose-containing dispersion of this embodiment has an appropriate viscosity adjusting ability, and by adding the fine fibrous cellulose-containing dispersion to a paint, the dispersion stability of particles such as pigments in the paint (hereinafter also simply referred to as "dispersion stability") can be improved. In other words, the fine fibrous cellulose-containing dispersion of this embodiment can impart excellent coating suitability and dispersibility stability to the paint by improving the dispersion stability of particles in the paint while keeping the thixotropy within an appropriate range.
[0014] The fibrous cellulose-containing dispersion of the present embodiment is preferably prepared by dispersing fibrous cellulose in a solvent containing water, and is more preferably an aqueous dispersion containing fine fibrous cellulose dispersed in water. In addition to water, the solvent may contain water-miscible organic solvents such as acetone, methanol, ethanol, and isopropanol. The content of such organic solvents is preferably 30% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less, of the total solvent. It is particularly preferable that the solvent does not contain any of these organic solvents (0% by mass).
[0015] The fine fibrous cellulose-containing dispersion of this embodiment is preferably used for paint, and as described above, the coating suitability of the paint can be improved. In addition, when the fine fibrous cellulose-containing dispersion of this embodiment is used as an additive for paint, the smoothness and design of the coating film after coating can be improved. Specifically, in this embodiment, a coating film with a smooth surface can be obtained. The smoothness of the coating film can be evaluated by the surface roughness (Ra) of the coating film, and when the surface roughness (Ra) of the coating film is 0.30 μm or less, the surface can be evaluated as being smooth. The surface roughness (Ra) of the coating film is preferably 0.10 μm or more, more preferably 0.12 μm or more. The surface roughness (Ra) of the coating film is more preferably 0.28 μm or less, and even more preferably 0.20 μm or less. The surface roughness (Ra) of the coating film was measured using an optical interference non-contact surface profiler (Ryoka Systems Co., Ltd., non-contact surface / layer cross-sectional profile measuring system VertScan2.0, model: R5500GML) with a ×10 objective lens to measure the arithmetic mean roughness (Ra) of the cured coating film over a measurement range of 470.92 μm × 353.16 μm.
[0016] When the fine fibrous cellulose-containing dispersion of the present embodiment is used as an additive for a coating material, the generation of aggregates in the coating film can be suppressed. Therefore, the design of the resulting coating film can be improved. In addition, the generation of aggregates in the coating film can be suppressed, thereby improving the smoothness and strength of the coating film.
[0017] The content of fine fibrous cellulose in the fibrous cellulose-containing dispersion is 1.5% by mass or more, preferably 1.8% by mass or more, more preferably 2.0% by mass or more, even more preferably more than 2.0% by mass, and even more preferably 2.1% by mass or more, based on the total mass of the fibrous cellulose-containing dispersion. The content of fine fibrous cellulose is less than 5.0% by mass, preferably 4.5% by mass or less, more preferably 4.0% by mass or less, even more preferably 3.5% by mass or less, even more preferably 3.0% by mass or less, even more preferably less than 3.0% by mass, and particularly preferably 2.9% by mass or less, based on the total mass of the fibrous cellulose-containing dispersion. When the content of fine fibrous cellulose is within the above range, the fibrous cellulose-containing dispersion liquid is prepared with excellent handling properties and can be obtained at a desired concentration without a concentration step, which is preferable.Furthermore, the fine fibrous cellulose is excellent in dispersibility in the dispersion liquid, and a dispersion liquid with excellent transparency is obtained, which is preferable.
[0018] The viscosity (η) of the dispersion containing fibrous cellulose at a rotation speed of 3 rpm using a Brookfield viscometer β From the viewpoint of fiber dispersibility and particle dispersibility of the dispersion, the viscosity (η β From the viewpoint of defoaming ability and suppression of the generation of coating film agglomerates, the viscosity (η β The details of the measurement conditions of '2) are the same as those described in the Examples.
[0019] The viscosity (η) of the dispersion containing fibrous cellulose at a rotation speed of 0.3 rpm using a Brookfield viscometer β From the viewpoint of fiber dispersibility and particle dispersibility of the dispersion, the viscosity (η β From the viewpoint of defoaming ability and suppression of the occurrence of coating film agglomerates, the viscosity (η βThe details of the measurement conditions of '1) are the same as those described in the Examples.
[0020] The ratio of the viscosity of the fibrous cellulose-containing dispersion is the ratio of the viscosity at a rotation speed of 0.3 rpm using a Brookfield viscometer to the viscosity at a rotation speed of 3 rpm using a Brookfield viscometer (i.e., η β '1 / η β From the viewpoint of obtaining a suitable thixotropy, '2) is preferably 5.00 or more, more preferably 6.00 or more, even more preferably 6.50 or more, and even more preferably 6.70 or more. From the viewpoint of coatability and suppression of the occurrence of coating film agglomerates, the viscosity ratio is preferably 7.40 or less, more preferably 7.30 or less, even more preferably 7.00 or less, and even more preferably 6.90 or less.
[0021] Viscosity of the fibrous cellulose-containing dispersion at a shear rate of 1 sec in a rheometer -1 Viscosity (η α From the viewpoint of fiber dispersibility and particle dispersibility of the dispersion, the viscosity (η α From the viewpoint of defoaming ability and suppression of the generation of coating film aggregates, the viscosity (η α The details of the measurement conditions of '1) are the same as those described in the Examples.
[0022] Viscosity of the fibrous cellulose-containing dispersion at a shear rate of 1000 sec -1 Viscosity (η αFrom the viewpoint of fiber dispersibility and particle dispersibility of the dispersion, the viscosity (η α From the viewpoints of defoaming ability and suppression of the occurrence of coating film agglomerates, the viscosity (η α The details of the measurement conditions of '2) are the same as those described in the Examples.
[0023] The viscosity ratio of the fibrous cellulose-containing dispersion is measured at a shear rate of 1000 sec -1 Viscosity (η α '2) Shear rate in rheometer: 1 sec -1 Viscosity (η α '1) ratio (i.e., η α '1 / η α From the viewpoint of obtaining suitable thixotropy, '2) is preferably at least 200, more preferably at least 300, even more preferably at least 400, still more preferably at least 450, and particularly preferably at least 470. Moreover, from the viewpoint of coatability and suppression of the occurrence of coating film agglomerates, the viscosity ratio is preferably at most 1000, more preferably at most 700, even more preferably at most 600, and still more preferably at most 500.
[0024] In this embodiment, the viscosity change rate when the fibrous cellulose-containing dispersion is diluted with a dispersion solvent containing water and isopropanol to obtain a dispersion having a water to isopropanol mass ratio of 7:3 and a viscosity of 2500 mPa s at 23°C and stirred under the following conditions is preferably within ±50%. Note that in this specification and this embodiment, "within ±50%" means "-50% or more and +50% or less." (Mixing conditions) A dispersion with a viscosity of 2500 mPa s at 23°C is poured into a cylindrical container with a diameter of 10 cm to a height of 5 cm. It is stirred for 24 hours at 23°C using an elliptical stirrer that is 5 cm long, 2 cm wide at the centre and 1 cm wide at the ends, while maintaining a 2 cm depression in the centre of the liquid surface. Usually, the viscosity change rate of the dispersion is often decreased by applying shear to the dispersion, so the viscosity change rate calculated by the above formula is often a negative value. In other words, it is more preferable that the viscosity change rate of the dispersion is -50% or more and 0% or less. The viscosity change rate of the dispersion calculated by the above formula is more preferably -40% or more, even more preferably -35% or more, and particularly preferably -30% or more, from the viewpoint of achieving both a low viscosity change rate and the ability to adjust the viscosity by adding fine fibrous cellulose, and of obtaining a fibrous cellulose-containing dispersion that is excellent in transparency, defoaming properties and particle dispersibility when contained in a paint, and is still more preferably -5% or less, even more preferably -10% or less, even more preferably -15% or less, and particularly preferably -18% or less. The viscosity change rate of the dispersion calculated by the above formula can be achieved, for example, by controlling the type and conditions of treatment for the fine fibrous cellulose, the degree of polymerization of the fine fibrous cellulose, the amount of ionic substituents, and the like, each within an appropriate range.
[0025] In this specification, the viscosity before and after stirring used to calculate the viscosity change rate of the dispersion is the viscosity value measured 1 minute after the start of measurement using a Brookfield viscometer at 23°C and a rotation speed of 6 rpm. As the Brookfield viscometer, for example, an analog viscometer T-LVT manufactured by BLOOKFIELD can be used. The viscosity before stirring is the viscosity of a dispersion adjusted to have a viscosity of about 2500 mPa·s, so the actual viscosity value of the dispersion is preferably 2500 mPa·s, but an error of about ±15% may occur. That is, in the calculation formula for the viscosity change rate, the viscosity before stirring is the actual viscosity of a dispersion adjusted to have a viscosity of about 2500 mPa·s, and is the actual viscosity value measured 1 minute after the start of measurement using a Brookfield viscometer at 23°C and a rotation speed of 6 rpm. However, when measuring the viscosity before stirring, the fine fibrous cellulose dispersion is poured into a cylindrical container with a diameter of 10 cm to a height of 5 cm, stirred with a disperser at 1500 rpm for 5 minutes, and the measurement is performed 1 minute after the end of stirring. In addition, when adjusting the viscosity of the dispersion before stirring to about 2500 mPa·s, the amount of fine fibrous cellulose used is appropriately adjusted. For example, the viscosity of the dispersion before stirring can be adjusted to about 2500 mPa·s by adjusting the content of fine fibrous cellulose to 0.2 to 3.0 mass% relative to the total mass of the dispersion.
[0026] In the calculation formula of the viscosity change rate, when measuring the viscosity after stirring, first, the dispersion liquid used for the viscosity measurement before stirring is further stirred with a stirrer. In this case, the dispersion liquid before stirring is placed in a cylindrical container with a diameter of 10 cm to a height of 5 cm of fine fibrous cellulose dispersion, and stirred for 24 hours using an elliptical stirrer with a length of 5 cm, width of the center of 2 cm, and width of the end of 1 cm, while maintaining a state in which the center of the liquid surface is depressed by 2 cm. The liquid temperature during stirring is kept at 23°C. Then, 1 minute after the end of stirring, the viscosity is measured using a B-type viscometer, and the viscosity value 1 minute after the start of measurement at 23°C and a rotation speed of 6 rpm is taken as the viscosity after stirring.
[0027] When preparing a dispersion for measuring the viscosity before and after stirring, the fibrous cellulose is diluted with a dispersion solvent containing water and isopropanol. In this case, the fibrous cellulose-containing dispersion is preferably an aqueous dispersion, and in this case, it is preferable to add water to the fibrous cellulose-containing dispersion as necessary, and then add isopropanol. If a sufficient amount of water is present in the fibrous cellulose-containing dispersion, only isopropanol may be added. In this way, the dispersion is prepared so that the ratio of the total mass of the water contained in the fibrous cellulose-containing dispersion and the water added as necessary to the mass of the isopropanol added is 7:3.
[0028] When the fibrous cellulose-containing dispersion is diluted with water to a fine fibrous cellulose concentration of 0.4% by mass to prepare a dispersion, the viscosity of the diluted dispersion at 23°C is preferably 20mPa·s or more, more preferably 200mPa·s or more, even more preferably 300mPa·s or more, even more preferably 350mPa·s or more, even more preferably 400mPa·s or more, even more preferably 600mPa·s or more, even more preferably 1000mPa·s or more, particularly preferably 1500mPa·s or more, and most preferably 1900mPa·s or more, from the viewpoint of functioning as a viscosity modifier when added to a coating material and improving the dispersion stability of the particles. Also, from the same viewpoint, the viscosity of the dispersion at 23°C is preferably 4700mPa·s or less, more preferably 4000mPa·s or less, even more preferably 3500mPa·s or less, even more preferably 3000mPa·s or less, and even more preferably 2500mPa·s or less. The viscosity of the diluted dispersion with a fine fibrous cellulose concentration of 0.4% by mass can be measured using a B-type viscometer (analog viscometer T-LVT, manufactured by BLOOKFIELD Corp.) The measurement conditions are 23°C and a rotation speed of 3 rpm, and the viscosity is measured 3 minutes after the start of the measurement.
[0029] When the fibrous cellulose-containing dispersion is diluted with water to a fine fibrous cellulose concentration of 0.2% by mass to prepare an aqueous dispersion, the haze of the diluted dispersion is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, and even more preferably 9.5% or less. The haze of the diluted dispersion in the above range means that the transparency of the fibrous cellulose-containing dispersion is high and the fine fibrous cellulose is well refined. When such a fibrous cellulose-containing dispersion is added to a coating material, the coating material can exhibit excellent coating suitability. Here, the haze of the fibrous cellulose-containing dispersion (fine fibrous cellulose concentration 0.2% by mass) is measured by putting the diluted fibrous cellulose dispersion into a glass cell for liquids (manufactured by Fujiwara Seisakusho, MG-40, reverse light path) with an optical path length of 1 cm, and using a haze meter (manufactured by Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7136:2000. The zero point measurement is performed using ion-exchanged water placed in the same glass cell.
[0030] <Fine fibrous cellulose> The fibrous cellulose contained in the fibrous cellulose-containing dispersion of this embodiment will be described below. The fibrous cellulose has a fiber width of 1000 nm or less and has an ionic substituent, the amount of the ionic substituent being 0.10 mmol / g or more and 1.50 mmol / g or less, and the degree of polymerization of the fibrous cellulose being 150 or more and 515 or less. In this embodiment, the fibrous cellulose is fine fibrous cellulose having a fiber width of 1000 nm or less. The fiber width of the fibrous cellulose is more preferably 100 nm or less, and even more preferably 8 nm or less.
[0031] The fiber width of fibrous cellulose can be measured, for example, by electron microscope observation. The average fiber width of fibrous cellulose is, for example, 1000 nm or less. The average fiber width of fibrous cellulose is, for example, preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, even more preferably 2 nm or more and 10 nm or less, and particularly preferably 2 nm or more and 8 nm or less. By making the average fiber width of fibrous cellulose 2 nm or more, it is possible to suppress dissolution of cellulose molecules in water, and to more easily exhibit the effect of improving strength, rigidity, and dimensional stability due to fibrous cellulose. The fibrous cellulose is, for example, monofilamentous cellulose.
[0032] The average fiber width of fibrous cellulose is measured, for example, using an electron microscope as follows. First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% by mass or more and 0.1% by mass or less is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Next, observation is performed using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fiber to be observed. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.
[0033] For observation images that satisfy the above conditions, the width of the fibers that intersect with lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers that intersect with lines X and Y is read. In this manner, the width of at least 20 fibers x 2 x 3 = 120 fibers is read. The average value of the read fiber widths is then determined as the average fiber width of the fibrous cellulose.
[0034] The fiber length of the fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. The fiber length of the fibrous cellulose is preferably, for example, 0.15 μm or more and 0.2 μm or more. The fiber length of the fibrous cellulose is preferably, for example, 100 μm or less, 10 μm or less, and 1 μm or less. By setting the fiber length within the above range, the destruction of the crystalline region of the fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fibrous cellulose to an appropriate range. The fiber length of the fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.
[0035] The fibrous cellulose preferably has an I-type crystal structure. Here, the fact that the fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. This can be expected to provide even more excellent performance in terms of heat resistance and low linear thermal expansion coefficient. The degree of crystallinity can be determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0036] The axial ratio (fiber length / fiber width) of the fibrous cellulose is not particularly limited, but is preferably, for example, 20 to 10,000, more preferably 50 to 1,000, even more preferably 50 to 500, and even more preferably 50 to 250. By setting the axial ratio to the above lower limit or more, it is easy to form a sheet containing fine fibrous cellulose. In addition, sufficient thickening is easily obtained when a solvent dispersion is produced. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fibrous cellulose is treated as an aqueous dispersion, handling such as dilution is easy.
[0037] The fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. In particular, fine fibrous cellulose having both crystalline and non-crystalline regions and a high axial ratio is realized by a method for producing fine fibrous cellulose, which will be described later.
[0038] The fibrous cellulose in this embodiment has, for example, at least one of an ionic substituent and a nonionic substituent. From the viewpoint of improving the dispersibility of the fibers in the dispersion medium and increasing the defibration efficiency in the defibration treatment, it is more preferable that the fibrous cellulose has an ionic substituent. The ionic substituent may include, for example, either one or both of an anionic group and a cationic group. In addition, the nonionic substituent may include, for example, an alkyl group and an acyl group. In this embodiment, it is particularly preferable that the ionic substituent has an anionic group. Examples of the anionic group as the ionic substituent include an ester group or a substituent derived from an ester group (sometimes simply referred to as an ester group), a carboxy group or a substituent derived from a carboxy group (sometimes simply referred to as a carboxy group), etc. Examples of the ester group include a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group (sometimes simply referred to as a phosphorus oxoacid group), a sulfur oxoacid group or a substituent derived from a sulfur oxoacid group (sometimes simply referred to as a sulfur oxoacid group), etc.
[0039] The anionic group as the ionic substituent is preferably at least one selected from, for example, a phosphorus oxo acid group or a substituent derived from a phosphorus oxo acid group, a carboxy group or a substituent derived from a carboxy group, and a sulfur oxo acid group or a substituent derived from a sulfur oxo acid group, more preferably at least one selected from a phosphorus oxo acid group and a carboxy group, and particularly preferably a phosphorus oxo acid group. When added to a coating material, the fine fibrous cellulose having a phosphorus oxo acid group can exhibit better coating suitability. In addition, the anionic group as the ionic substituent is preferably an ester group from the viewpoint of the transparency of the dispersion, coating material, and coating film.
[0040] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). The phosphorus oxoacid group is, for example, a divalent functional group obtained by removing a hydroxyl group from phosphoric acid. Specifically, it is a group represented by -PO3H2. The substituent derived from the phosphorus oxoacid group includes a salt of the phosphorus oxoacid group, a phosphorus oxoacid ester group, and the like. The substituent derived from the phosphorus oxoacid group may be contained in the fibrous cellulose as a group in which a phosphoric acid group is condensed (for example, a pyrophosphate group). The phosphorus oxoacid group may be, for example, a phosphorous acid group (phosphonic acid group), and the substituent derived from the phosphorus oxoacid group may be a salt of the phosphorous acid group, a phosphorous acid ester group, or the like.
[0041] [ka]
[0042] In formula (1), a, b, and n are natural numbers (where a=b×m). 1 ,α 2 ,...,α n And a of α' are O - The rest are either R or OR. Note that each α n and all of α' are O - Each R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In addition, n is preferably 1.
[0043] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0044] In addition, examples of the derivative group in R include, but are not limited to, functional groups in which at least one of functional groups such as a carboxy group, a hydroxy group, or an amino group is added to or substituted for the main chain or side chain of the above-mentioned various hydrocarbon groups. In addition, the number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set within an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine fibrous cellulose.
[0045] β b+ is a monovalent or higher cation made of an organic or inorganic substance. Examples of the monovalent or higher cation made of an organic substance include aliphatic ammonium or aromatic ammonium, and examples of the monovalent or higher cation made of an inorganic substance include, but are not limited to, ions of alkali metals such as sodium, potassium, or lithium, cations of divalent metals such as calcium or magnesium, or hydrogen ions. These can be used alone or in combination of two or more kinds. Examples of the monovalent or higher cation made of an organic or inorganic substance include β b+Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing β is heated and are easy to use industrially, but are not particularly limited thereto. b+ may be an organic onium ion, in which case it is particularly preferably an organic ammonium ion.
[0046] The amount of ionic substituent introduced into fibrous cellulose (ionic substituent amount) may be 0.10 mmol / g or more per 1 g (mass) of fibrous cellulose, preferably 0.20 mmol / g or more, more preferably 0.30 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, even more preferably 0.60 mmol / g or more, and particularly preferably 0.70 mmol / g or more. The amount of ionic substituent introduced into fibrous cellulose may be 1.50 mmol / g or less per 1 g (mass) of fibrous cellulose, preferably 1.35 mmol / g or less, more preferably 1.20 mmol / g or less, and even more preferably 1.10 mmol / g or less. The amount of ionic substituent introduced into fibrous cellulose may be 1.00 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 0.95 mmol / g or less. Here, the denominator in the unit mmol / g is the counter ion of the ionic substituent, which is a hydrogen ion (H + ) indicates the mass of fibrous cellulose when the amount of ionic substituent introduced is within the above range, it is possible to improve the dispersion stability of the fibrous cellulose in the coating material. In addition, by controlling the amount of ionic substituent introduced within the above range, it is possible to control the thixotropy of the coating material when the fine fibrous cellulose is added to the coating material to an appropriate range, thereby more effectively improving the coating suitability.
[0047] The amount of ionic substituent introduced into the fibrous cellulose can be measured, for example, by neutralization titration. In the measurement by neutralization titration, an alkali such as an aqueous sodium hydroxide solution is added to the obtained slurry containing the fibrous cellulose, and the amount introduced is measured by determining the change in pH.
[0048] 1 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fibrous cellulose is measured, for example, as follows. First, a slurry containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 1 is obtained. In the titration curve shown in the upper part of Figure 1, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 1, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH against the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total amount of dissociated acid of the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxo acid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxo acid group introduced (or the amount of phosphorus oxo acid group), it refers to the amount of the first dissociated acid. In FIG. 1, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0049] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with an arbitrary cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: total amount of anions derived from phosphorus oxoacid groups in fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (e.g., Na is 23, Al is 9)
[0050] 2 is a graph showing the relationship between the amount of NaOH dropped onto a dispersion containing fibrous cellulose having a carboxy group as an ionic substituent and the pH. The amount of carboxy group introduced into the fibrous cellulose is measured, for example, as follows. First, a dispersion liquid containing fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, a defibration treatment similar to the defibration treatment step described below may be performed on the measurement target prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve as shown in the upper part of FIG. 2 is obtained. In the titration curve shown in the upper part of FIG. 2, the measured pH is plotted against the amount of added alkali, and in the titration curve shown in the lower part of FIG. 2, the increment (differential value) (1 / mmol) of pH against the amount of added alkali is plotted. In this neutralization titration, one point where the increment (differential value of pH against the amount of added alkali) is maximum is confirmed in the curve plotting the measured pH against the amount of added alkali, and this maximum point is called the first end point. Here, the region from the start of titration to the first end point in FIG. 2 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the dispersion used for titration. The amount of alkali required in the first region of the titration curve (mmol) is divided by the solid content (g) in the dispersion containing the fibrous cellulose to be titrated to calculate the amount of carboxyl groups introduced (mmol / g).
[0051] The above-mentioned amount of carboxyl groups introduced (mmol / g) indicates the amount of carboxyl groups in the acid-type fibrous cellulose (hereinafter referred to as the amount of carboxyl groups (acid type)) since the denominator is the mass of the acid-type fibrous cellulose. On the other hand, when the counter ion of the carboxyl group is replaced with any cation C so as to be the charge equivalent, the amount of carboxyl groups in the fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of carboxyl groups (C type)) can be obtained by converting the denominator to the mass of the fibrous cellulose when the cation C is the counter ion. That is, it is calculated by the following formula. Carboxylic acid amount (C type) = Carboxylic acid amount (acid type) / {1 + (W-1) x (Carboxylic acid amount (acid type)) / 1000} W: Formula weight per valence of cation C (e.g., Na is 23, Al is 9)
[0052] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of ionic substituents may be lower than the actual amount, and an accurate value may not be obtained. As an appropriate amount of drop and titration interval, for example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the fibrous cellulose-containing slurry, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0053] The amount of sulfur oxoacid groups introduced into the fine fibrous cellulose is measured by wet ashing of the sample and ICP emission spectrometry. Specifically, the fibrous cellulose-containing slurry is dried and then weighed, perchloric acid is added, carbonized, and concentrated nitric acid is added to oxidize the carbon to carbon dioxide, to obtain a sample solution consisting only of inorganic substances. This sample solution is then diluted at an appropriate ratio, and the sulfate ion concentration is measured by ICP emission spectrometry. The amount of sulfur atoms contained in the sample solution is then divided by the weighed dry mass of the fibrous cellulose to obtain the amount of sulfur oxoacid groups (unit: mmol / g).
[0054] The polymerization degree of the fine fibrous cellulose may be 150 or more, preferably 200 or more, more preferably 300 or more, more preferably 320 or more, even more preferably 340 or more, even more preferably 360 or more, even more preferably 380 or more, even more preferably 400 or more, and particularly preferably 460 or more. The polymerization degree of the fine fibrous cellulose may be 515 or less, preferably 500 or less, and more preferably 490 or less. By making the polymerization degree of the fine fibrous cellulose within the above range, the thixotropy of the paint when the fine fibrous cellulose is added to the paint can be reduced (low thixotropy) to an appropriate range, and thus the coating suitability can be more effectively improved. In addition, by making the polymerization degree of the fine fibrous cellulose within the above range, the smoothness, designability, and strength of the coating film can be more effectively improved. Furthermore, by making the polymerization degree within the above range, the transparency of the fibrous cellulose-containing dispersion is improved, which is preferable.
[0055] The degree of polymerization of fine fibrous cellulose is a value calculated from the pulp viscosity measured according to Tappi T 230. Specifically, the fine fibrous cellulose to be measured is dispersed in an aqueous copper ethylenediamine solution to measure the viscosity (referred to as η1), and the blank viscosity (referred to as η0) is measured using only the dispersion medium, and then the specific viscosity (ηsp) and intrinsic viscosity ([η]) are measured according to the following formula. ηsp=(η1 / η0)-1 [η]=ηsp / (c(1+0.28×ηsp)) Here, c in the formula represents the concentration (g / mL) of the fine fibrous cellulose at the time of viscosity measurement. Furthermore, the degree of polymerization (DP) is calculated from the following formula. DP = 1.75 × [η] Since this degree of polymerization is an average degree of polymerization measured by a viscosity method, it is sometimes called the "viscosity average degree of polymerization."
[0056] In this embodiment, preferably, the degree of polymerization of the fine fibrous cellulose is 300 to 515, and the amount of ionic substituents in the fine fibrous cellulose is 0.40 mmol / g to 1.20 mmol / g, and more preferably, the degree of polymerization of the fine fibrous cellulose is 460 to 490, and the amount of ionic substituents in the fine fibrous cellulose is 0.70 mmol / g to 0.95 mmol / g, thereby reducing the thixotropy of the paint when the fine fibrous cellulose is added to the paint and improving the particle dispersibility, thereby more effectively improving the coating suitability of the paint. Setting the degree of polymerization of the fine fibrous cellulose and the amount of ionic substituents in the appropriate ranges contributes to improving the particle dispersibility while the dispersion in which the fine fibrous cellulose is dispersed exhibits low thixotropy, and is therefore considered to improve the coating suitability of the paint.
[0057] (Method of producing a dispersion containing fine fibrous cellulose) [Method for producing fine fibrous cellulose] <Textile raw materials> Fine fibrous cellulose is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), and mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP). Examples of non-wood pulp include, but are not particularly limited to, cotton-based pulp such as cotton linters and cotton lint, and non-wood-based pulp such as hemp, wheat straw, and bagasse. The deinked pulp is not particularly limited, and may be deinked pulp made from waste paper. The pulp of this embodiment may be one of the above, or a mixture of two or more. Among the above pulps, wood pulp and deinked pulp are preferable from the viewpoint of availability. Among wood pulps, chemical pulp is more preferable, and kraft pulp and sulfite pulp are even more preferable, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and of small decomposition of cellulose in the pulp and of obtaining long-fiber fine fibrous cellulose with a large axial ratio. The viscosity tends to be high when long-fiber fine fibrous cellulose with a large axial ratio is used.
[0058] As the fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of the fiber raw material containing cellulose, fibers formed from linear nitrogen-containing polysaccharide polymers such as chitin and chitosan can be used.
[0059] <Phosphorus oxo acid group introduction step> The process for producing fine fibrous cellulose includes a step of introducing an ionic substituent. An example of the step of introducing an ionic substituent is a step of introducing a phosphorus oxoacid group. The step of introducing a phosphorus oxoacid group is a step of reacting a hydroxyl group in a fiber raw material containing cellulose with at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing a phosphorus oxoacid group, on the fiber raw material containing cellulose. This step results in the production of a fiber into which a phosphorus oxoacid group has been introduced.
[0060] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B"). Alternatively, the reaction of the cellulose-containing fiber raw material with compound A may be carried out in the absence of compound B.
[0061] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, since the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use, for example, a cotton-like or thin sheet-like form. Compound A and compound B can be added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, since the reaction is highly uniform. In addition, compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution state, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0062] The compound A used in this embodiment may be any compound having a phosphorus atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of the phosphoric acid include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high introduction efficiency of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid, sodium phosphite are more preferred.
[0063] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0064] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0065] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0066] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0067] In the phosphorus oxo acid group introduction step, it is preferable to add or mix the compound A or the like to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, and a high-frequency dryer.
[0068] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A is attracted to the water molecules by surface tension and similarly moves to the surface of the fiber raw material (i.e., unevenness in the concentration of compound A is caused).
[0069] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated by the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0070] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0071] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be carried out twice or more. By carrying out the phosphorus oxo acid group introduction step twice or more, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material.
[0072] The amount of phosphorus oxo acid group introduced into the fiber raw material may be, for example, 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, preferably 0.20 mmol / g or more, more preferably 0.30 mmol / g or more, more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, even more preferably 0.60 mmol / g or more, and particularly preferably 0.70 mmol or more. The amount of phosphorus oxo acid group introduced into the fiber raw material may be, for example, 1.50 mmol / g or less per 1 g (mass) of fine fibrous cellulose, preferably 1.35 mmol / g or less, more preferably 1.20 mmol / g or less, and even more preferably 1.10 mmol / g or less. The amount of phosphorus oxo acid group introduced into the fibrous cellulose may be, for example, 1.00 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 0.95 mmol / g or less. By controlling the amount of phosphorus oxoacid groups introduced within the above range, it is possible to improve the dispersion stability of the fine fibrous cellulose in the coating material. Also, by controlling the amount of phosphorus oxoacid groups introduced within the above range, the thixotropy of the coating material when the fine fibrous cellulose is added to the coating material can be reduced to an appropriate range, and the dispersion stability of the particles can be improved, thereby more effectively improving the coating suitability.
[0073] <Carboxy group introduction step> The process for producing fine fibrous cellulose may include, for example, a carboxyl group introduction step as an ionic substituent introduction step. The carboxyl group introduction step is carried out by subjecting a fiber raw material containing cellulose to an oxidation treatment such as ozone oxidation, oxidation by the Fenton method, or TEMPO oxidation treatment, or treating the raw material with a compound having a carboxylic acid-derived group or a derivative thereof, or an acid anhydride of a compound having a carboxylic acid-derived group or a derivative thereof.
[0074] Examples of compounds having a group derived from a carboxylic acid include, but are not limited to, dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid. Examples of derivatives of compounds having a group derived from a carboxylic acid include, but are not limited to, imidized products of acid anhydrides of compounds having a carboxy group, and derivatives of acid anhydrides of compounds having a carboxy group. Examples of imidized products of acid anhydrides of compounds having a carboxy group include, but are not limited to, imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.
[0075] The acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, etc. Furthermore, the derivative of an acid anhydride of a compound having a group derived from a carboxylic acid is not particularly limited, but examples thereof include acid anhydrides of compounds having a carboxy group such as dimethylmaleic anhydride, diethylmaleic anhydride, diphenylmaleic anhydride, etc., in which at least a part of the hydrogen atoms is substituted with a substituent such as an alkyl group or a phenyl group.
[0076] When the TEMPO oxidation treatment is performed in the carboxyl group introduction step, it is preferable to perform the treatment under conditions of pH 6 or more and 8 or less. Such a treatment is also called neutral TEMPO oxidation treatment. The neutral TEMPO oxidation treatment can be performed, for example, by adding pulp as a fiber raw material, a nitroxy radical such as TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) as a catalyst, and sodium hypochlorite as a sacrificial reagent to a sodium phosphate buffer solution (pH = 6.8). By further adding sodium chlorite, the aldehyde generated in the oxidation process can be efficiently oxidized to a carboxyl group. The TEMPO oxidation treatment may also be performed under conditions of pH 10 or more and 11 or less. Such a treatment is also called alkaline TEMPO oxidation treatment. The alkaline TEMPO oxidation treatment can be performed, for example, by adding a nitroxy radical such as TEMPO as a catalyst, sodium bromide as a co-catalyst, and sodium hypochlorite as an oxidizing agent to pulp as a fiber raw material.
[0077] The amount of carboxyl groups introduced into the fibrous cellulose varies depending on the type of the substituent, but for example, when the carboxyl groups are introduced by TEMPO oxidation, it is sufficient that the amount is 0.10 mmol / g or more per 1 g (mass) of fine fibrous cellulose, preferably 0.20 mmol / g or more, more preferably 0.30 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, and particularly preferably 0.60 mmol / g or more. The amount of carboxyl groups introduced into the fibrous cellulose is sufficient that the amount is 1.50 mmol / g or less, preferably 1.35 mmol / g or less, more preferably 1.20 mmol / g or less, and even more preferably 1.10 mmol / g or less. The amount of carboxyl groups introduced into the fibrous cellulose is also preferably 1.00 mmol / g or less per 1 g (mass) of fibrous cellulose, more preferably 0.95 mmol / g or less. By setting the amount of carboxyl groups introduced within the above range, it is possible to increase the dispersion stability of the fine fibrous cellulose in the coating material. Furthermore, by keeping the amount of carboxyl groups introduced within the above range, the thixotropy of the paint when the fine fibrous cellulose is added to the paint can be reduced to an appropriate range, thereby more effectively improving the coating suitability.
[0078] <Sulfur oxoacid group introduction step> The process for producing fine fibrous cellulose may include, for example, a sulfur oxoacid group introduction step as an ionic substituent introduction step, in which a hydroxyl group in a fiber raw material containing cellulose reacts with a sulfur oxoacid to obtain cellulose fibers having sulfur oxoacid groups (sulfur oxoacid group-introduced fibers).
[0079] In the sulfur oxo acid group introduction step, instead of compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing sulfur oxo acid groups by reacting with hydroxyl groups of fiber raw materials containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As sulfuric acid, sulfuric acid of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As sulfurous acid, 5% sulfurous acid water may be used. As sulfates or sulfites, lithium salts, sodium salts, potassium salts, ammonium salts of sulfates or sulfites may be used, and these may have various degrees of neutralization. As sulfuric acid amides, sulfamic acid or the like may be used. In the sulfur oxo acid group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0080] In the sulfur oxoacid group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfur oxoacid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a heat-treatment temperature that allows efficient introduction of sulfur oxoacid groups while suppressing thermal decomposition and hydrolysis of the fibers. The heat-treatment temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. The heat-treatment temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0081] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfur oxoacid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, equipment having various heat media can be used, such as a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.
[0082] The amount of sulfur oxoacid groups introduced into the cellulose raw material may be 0.10 mmol / g or more, preferably 0.20 mmol / g or more, more preferably 0.30 mmol / g or more, even more preferably 0.40 mmol / g or more, even more preferably 0.50 mmol / g or more, even more preferably 0.60 mmol / g or more, and even more preferably 0.70 mmol / g or more. The amount of sulfur oxoacid groups introduced into the cellulose raw material may be 1.50 mmol / g or less, preferably 1.35 mmol / g or less, more preferably 1.20 mmol / g or less, and even more preferably 1.10 mmol / g or less. The amount of sulfur oxoacid groups introduced into the fibrous cellulose may be 1.00 mmol / g or less per gram (mass) of fibrous cellulose, and more preferably 0.95 mmol / g or less. By controlling the amount of sulfur oxoacid groups introduced within the above range, it is possible to improve the dispersion stability of the fine fibrous cellulose in the coating material. Also, by controlling the amount of sulfur oxoacid groups introduced within the above range, it is possible to reduce the thixotropy of the coating material when the fine fibrous cellulose is added to the coating material and to set it within an appropriate range, thereby more effectively improving the coating suitability.
[0083] <Cleaning process> In the method for producing fine fibrous cellulose in this embodiment, a washing step can be carried out on the ionic substituent-introduced fiber as necessary. The washing step is carried out, for example, by washing the ionic substituent-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0084] <Alkaline treatment process> When producing fine fibrous cellulose, an alkali treatment may be carried out on the fiber raw material between the step of introducing an ionic substituent and the step of defibrating the fiber, which will be described later. The method of the alkali treatment is not particularly limited, but may be, for example, a method of immersing the fiber having an ionic substituent introduced therein in an alkali solution.
[0085] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0086] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, 5° C. to 80° C., and more preferably, 10° C. to 60° C. The time for immersing the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably, 5 minutes to 30 minutes, and more preferably, 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably, 100 mass% to 100,000 mass%, and more preferably, 1000 mass% to 10,000 mass%, based on the absolute dry mass of the ionic substituent-introduced fiber.
[0087] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the ionic substituent-introduced fiber may be washed with water or an organic solvent after the ionic substituent-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated ionic substituent-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0088] <Acid treatment process> When producing fine fibrous cellulose, the fiber raw material may be subjected to an acid treatment between the step of introducing an ionic substituent and the defibration treatment step described later. For example, the step of introducing an ionic substituent, the acid treatment, the alkali treatment, and the defibration treatment may be performed in this order.
[0089] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0090] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, 5° C. to 100° C., and more preferably, 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is preferably, for example, 5 minutes to 120 minutes, and more preferably, 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is preferably, for example, 100 mass% to 100,000 mass%, and more preferably, 1000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material.
[0091] <Defibrillation processing> The ionic substituent-introduced fibers are defibrated in a defibration process to obtain fine fibrous cellulose. In the defibration process, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0092] In the defibration process, for example, it is preferable to dilute the ionic substituent-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0093] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the ionic substituent-introduced fibers in a dispersion medium may contain solids other than the ionic substituent-introduced fibers, such as urea having hydrogen bonding properties. The solid content concentration of the fine fibrous cellulose during the defibration treatment and the thixotropy reduction treatment described later is preferably the same as the concentration of the fibrous cellulose-containing dispersion of this embodiment. In addition, it is also preferable that the concentration of the cellulose-containing dispersion is the same as the solid content concentration of the cellulose during the defibration treatment and the thixotropy reduction treatment, in that a process such as concentration is not required.
[0094] <Low thixotropy treatment> The method for producing a fibrous cellulose-containing dispersion of the present embodiment preferably includes a step of performing a thixotropy-reducing treatment in addition to the steps described above. Specifically, as described above, it is preferable to include a step of performing a defibration treatment on cellulose fibers that have been appropriately treated to obtain fibrous cellulose with a fiber width of 1000 nm or less, and a step of performing a thixotropy-reducing treatment on the fibrous cellulose. That is, the method for producing a fibrous cellulose-containing dispersion of the present embodiment preferably includes, for example, a step of performing a thixotropy-reducing treatment on cellulose fibers after performing a defibration treatment on the cellulose fibers. Note that, as described above, it is preferable to further include a step of introducing an ionic substituent into the cellulose fibers before the defibration treatment step, and in the step of introducing the ionic substituent, the ionic substituent is introduced so that the amount of the ionic substituent in the fibrous cellulose is 0.10 mmol / g or more and 1.50 mmol / g or less. Note that, in addition to the step of introducing the ionic substituent, it is also preferable to further include a washing step or an alkali treatment step before the defibration treatment step. In addition, since the amount of ionic substituents in the fine fibrous cellulose hardly changes even after the thixotropy reduction treatment, the amount of ionic substituents in the fine fibrous cellulose before the thixotropy reduction treatment can be approximated as the amount of ionic substituents in the fine fibrous cellulose after the thixotropy reduction treatment.
[0095] In this specification, the step of performing the low thixotropy treatment is a step of performing a treatment to reduce the thixotropy of the dispersion containing fine fibrous cellulose to an appropriate range. Specifically, the step of performing the low thixotropy treatment is a step of reducing the degree of polymerization of fibrous cellulose having a fiber width of 1000 nm or less to 150 or more and 515 or less. Therefore, the low thixotropy treatment can also be called a low polymerization degree treatment. The degree of polymerization of the fine fibrous cellulose obtained by the low thixotropy treatment may be 150 or more, preferably 200 or more, more preferably 300 or more, even more preferably 320 or more, even more preferably 340 or more, even more preferably 360 or more, even more preferably 380 or more, even more preferably 400 or more, and particularly preferably 460 or more. The degree of polymerization of the fine fibrous cellulose obtained in the step of carrying out the low thixotropy treatment may be 515 or less, preferably 500 or less, and more preferably 490 or less.
[0096] Examples of the process for carrying out the low thixotropy treatment include an ozone treatment process, an enzyme treatment process, a hypochlorous acid treatment process, and a subcritical water treatment process. The process for carrying out the low thixotropy treatment is preferably at least one selected from an ozone treatment process, an enzyme treatment process, a hypochlorous acid treatment process, and a subcritical water treatment process, and is particularly preferably an ozone treatment process. Note that what is common to the ozone treatment process, the enzyme treatment process, the hypochlorous acid treatment process, and the subcritical water treatment process is the reduction in the degree of polymerization, and the reduction in the degree of polymerization is the reduction in the thixotropy treatment, resulting in the production of a fibrous cellulose-containing dispersion in this embodiment.
[0097] In the ozone treatment step, ozone is added to the fine fibrous cellulose dispersion (slurry). When adding ozone, it is preferable to add it as an ozone / oxygen mixed gas, for example. In this case, the ozone addition rate per 1 g of fine fibrous cellulose contained in the fine fibrous cellulose dispersion (slurry) is 1.0×10 -4 g or more, and 1.0×10 -3The ozone addition rate per 1 g of fine fibrous cellulose is preferably 1.0×10 1 g or less, and 1.0×10 0 g or less, and more preferably 1.0×10 -1 g or less, and more preferably 3.0×10 -2 g or less, and more preferably 1.5×10 -2 It is even more preferable that the thickness is 1.0×10 -2 g or less, and more preferably 6.0×10 -3 After adding ozone to the fine fibrous cellulose dispersion (slurry), it is preferable to stir the mixture at 10° C. to 50° C. for 10 seconds to 10 minutes, and then leave the mixture to stand for 1 minute to 100 minutes.
[0098] In the enzyme treatment step, an enzyme is added to the fine fibrous cellulose dispersion (slurry). The enzyme used in this step is preferably a cellulase enzyme. Cellulase enzymes are classified into a carbohydrate hydrolase family based on the higher-order structure of the catalytic domain that has the function of hydrolyzing cellulose. Cellulase enzymes are broadly classified into endo-glucanase and cellobiohydrolase according to their cellulose decomposition properties. Endo-glucanase has high hydrolysis ability for the amorphous part of cellulose, soluble cellooligosaccharides, and cellulose derivatives such as carboxymethylcellulose, and randomly cuts the molecular chains from the inside to reduce the degree of polymerization. In contrast, cellobiohydrolase decomposes the crystalline part of cellulose to give cellobiose. Cellobiohydrolase also hydrolyzes from the end of the cellulose molecule and is also called exo-type or processive enzyme. The enzyme used in the enzyme treatment step is not particularly limited, but it is preferable to use endo-glucanase.
[0099] In the enzyme treatment process, the enzyme addition rate was 1.0 × 10 per 1 g of fine fibrous cellulose. -7g or more, and 1.0×10 -6 g or more, and more preferably 5.0×10 -6 g or more, and more preferably 1.0×10 -5 The enzyme addition rate is preferably 1.0×10 to 1 g of fine fibrous cellulose. -2 After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferable to stir the mixture at 30° C. to 70° C. for 1 minute to 10 hours, and then place the mixture at 90° C. or higher to inactivate the enzyme.
[0100] In the hypochlorite treatment process, sodium hypochlorite is added to the fine fibrous cellulose dispersion (slurry). The sodium hypochlorite addition rate is 1.0×10 per 1 g of fine fibrous cellulose. -4 g or more, and 1.0×10 -3 g or more, and more preferably 1.0×10 -2 The sodium hypochlorite content is preferably 1.0×10 to 1 g of fine fibrous cellulose. 2 g or less, and preferably 1.0×10 1 g or less, and more preferably 3×10 0 After sodium hypochlorite is added to the fine fibrous cellulose dispersion (slurry), it is preferable to stir the mixture at 10° C. or higher and 50° C. or lower for 1 minute to 10 hours.
[0101] In the subcritical water treatment process, the fine fibrous cellulose dispersion (slurry) is subjected to high-temperature and high-pressure treatment to bring it into a subcritical state. The fine fibrous cellulose is hydrolyzed in the subcritical state. Specifically, the fine fibrous cellulose dispersion (slurry) is placed in a reaction vessel, and then heated to 150°C to 500°C, preferably 150°C to 350°C, and the pressure in the reaction vessel is increased to 10 MPa to 80 MPa, preferably 10 MPa to 20 MPa. The heating and pressurizing time is preferably 0.1 seconds to 100 seconds, more preferably 0.3 seconds to 50 seconds.
[0102] After the above-mentioned low thixotropy treatment, a second defibration treatment step may be further carried out. The second defibration treatment step may be the same as the above-mentioned defibration treatment step for obtaining fibrous cellulose having a fiber width of 1000 nm or less.
[0103] The fibrous cellulose-containing dispersion may contain, in addition to a solvent containing water and fine fibrous cellulose, other additives such as, for example, antifoaming agents, lubricants, ultraviolet absorbers, dyes, pigments, stabilizers, surfactants, and preservatives (e.g., phenoxyethanol).
[0104] (Application) The fibrous cellulose-containing dispersion of the present embodiment is preferably used as a thickener for various applications. For example, the fibrous cellulose-containing dispersion of the present embodiment can be used as an additive to food, cosmetics, cement, paint (for painting vehicles such as automobiles, ships, and aircraft, for building materials, for daily necessities, etc.), ink, medicine, etc. In addition, the fibrous cellulose-containing dispersion of the present embodiment can be applied to daily necessities by adding it to resin-based materials or rubber-based materials. Among them, the fibrous cellulose-containing dispersion of the present embodiment is particularly preferably a fibrous cellulose-containing dispersion for paint. EXAMPLES
[0105] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0106] <Production Example 1> [Production of phosphorylated fine fibrous cellulose dispersion] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 208 g / m) manufactured by Oji Paper Co., Ltd. 2 A sheet-like product with a Canadian Standard Freeness (CSF) of 700 mL when disintegrated and measured in accordance with JIS P 8121-2:2012 was used.
[0107] This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 140°C for 200 seconds to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0108] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0109] Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.
[0110] The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. -1 Absorption due to phosphate groups was observed in the vicinity, confirming that phosphate groups had been added to the pulp.
[0111] In addition, the obtained phosphorylated pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0112] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose.
[0113] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the method described in [Measurement of amount of phosphorus oxo acid groups] below was 0.80 mmol / g.
[0114] <Production Example 2> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the drying temperature of the chemical-impregnated pulp during phosphorylation was 140° C. and the drying time was 230 seconds. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.00 mmol / g.
[0115] <Production Example 3> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the drying temperature of the chemical-impregnated pulp during phosphorylation was 165° C. and the drying time was 170 seconds. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid groups] below was 1.20 mmol / g.
[0116] <Production Example 4> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the drying temperature of the chemical-impregnated pulp during phosphorylation was 165° C. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described later in [Measurement of amount of phosphorus oxo acid groups] was 1.45 mmol / g.
[0117] <Production Example 5> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 4, except that the phosphorylation treatment and the washing treatment were each performed once in this order on the washed phosphorylated pulp before the neutralization treatment. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described later in [Measurement of the amount of phosphorus oxo acid groups] was 2.00 mmol / g.
[0118] <Production Example 6> [Production of Phosphorous Fine Fibrous Cellulose Dispersion] The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 245 g / m) manufactured by Oji Paper. 2 A sheet-like product with a Canadian Standard Freeness (CSF) of 700 mL when disintegrated and measured in accordance with JIS P 8121-2:2012 was used.
[0119] This raw pulp was subjected to phosphorus oxo-oxidation treatment as follows. First, a mixed aqueous solution of phosphorous acid (phosphonic acid) and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to prepare 33 parts by mass of phosphorous acid (phosphonic acid), 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated in a hot air dryer at 165°C for 150 seconds to introduce phosphorous groups into the cellulose in the pulp, thereby obtaining a phosphorous-saturated pulp.
[0120] The resulting phosphorous-subtilized pulp was then washed. The washing was carried out by repeatedly pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorous-subtilized pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse the pulp, and then filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0121] Next, the washed phosphited pulp was subjected to a neutralization treatment as follows. First, the washed phosphited pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a phosphited pulp slurry having a pH of 12 to 13. Next, the phosphited pulp slurry was dehydrated to obtain a neutralized phosphited pulp. Next, the neutralized phosphited pulp was subjected to the above-mentioned washing treatment.
[0122] The infrared absorption spectrum of the phosphorous pulp obtained was measured using FT-IR. -1 Absorption due to the P=O of the phosphonic acid group, which is a tautomer of the phosphorous acid group, was observed near the nucleus, confirming that the phosphorous acid group (phosphonic acid group) was added to the pulp. In addition, when the obtained phosphorous-containing pulp was analyzed using an X-ray diffraction device, typical peaks were confirmed at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, confirming that it has cellulose type I crystals.
[0123] Ion-exchanged water was added to the obtained phosphorous-subtilized pulp to prepare a slurry having a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose.
[0124] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of phosphorous acid groups (amount of first dissociated acid) measured by the method described in [Measurement of phosphorus oxo acid group amount] below was 0.74 mmol / g.
[0125] <Production Example 7> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 6, except that the heating time of the chemical-impregnated pulp during the phosphorus hypodermic reaction was 220 seconds. The amount of phosphorous groups (amount of first dissociated acid) measured by the method described in [Measurement of amount of phosphorous oxo acid groups] below was 1.41 mmol / g.
[0126] <Production Example 8> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 6, except that the heating time of the chemical-impregnated pulp during the phosphite conversion was 400 seconds. The amount of phosphite groups (amount of first dissociated acid) measured by the measurement method described later in [Measurement of amount of phosphorus oxo acid groups] was 1.86 mmol / g.
[0127] <Production Example 9> A sulfated pulp was obtained by the same procedure as in Production Example 6, except that 38 parts by mass of amidosulfuric acid (sulfamic acid) was used instead of phosphorous acid (phosphonic acid) and the heating time was extended to 13 minutes.
[0128] The infrared absorption spectrum of the sulfated pulp obtained was measured using FT-IR. -1 Absorption due to sulfate groups was observed in the vicinity, confirming that sulfate groups had been added to the pulp.
[0129] In addition, the obtained sulfated pulp was analyzed using an X-ray diffractometer, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and 2θ = 22° to 23°, and it was confirmed that the sulfated pulp had cellulose type I crystals. Ion-exchanged water was added to the obtained sulfated pulp, and the mixture was stirred to make a 2% by mass slurry. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a slurry containing fine fibrous cellulose. X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3-5 nm. The amount of sulfate groups (sulfonic acid groups) measured by the method described in [Measurement of sulfur oxoacid group amount] below was 0.88 mmol / g.
[0130] <Production Example 10> [Production of TEMPO-oxidized fine fibrous cellulose dispersion] As the raw material pulp, softwood kraft pulp (undried) manufactured by Oji Paper Co., Ltd. was used. This raw material pulp was subjected to an alkaline TEMPO oxidation treatment as follows. First, the raw material pulp equivalent to 100 parts by mass of dry mass, 1.6 parts by mass of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl), and 10 parts by mass of sodium bromide were dispersed in 10,000 parts by mass of water. Next, a 13% by mass aqueous solution of sodium hypochlorite was added to 1.3 mmol per 1.0 g of pulp to start the reaction. During the reaction, a 0.5 M aqueous solution of sodium hydroxide was added dropwise to keep the pH at 10 to 10.5, and the reaction was deemed to be complete when no change in pH was observed.
[0131] The TEMPO oxidized pulp was then washed. The washing was performed by dehydrating the pulp slurry after TEMPO oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water into the sheet, stirring to disperse the sheet uniformly, and then filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0132] The remaining aldehyde groups in this dehydrated sheet were subjected to additional oxidation treatment as follows: 100 parts by weight of the above dehydrated sheet, equivalent to a dry weight, was dispersed in 10,000 parts by weight of 0.1 mol / L acetate buffer (pH 4.8). Next, 113 parts by weight of 80% sodium chlorite was added, and the mixture was immediately sealed, and then reacted at room temperature for 48 hours while stirring at 500 rpm using a magnetic stirrer to obtain a pulp slurry.
[0133] Next, the obtained TEMPO oxidized pulp after additional oxidation was subjected to a washing treatment. The washing treatment was carried out by dehydrating the pulp slurry after additional oxidation to obtain a dehydrated sheet, pouring 5,000 parts by mass of ion-exchanged water, stirring to disperse uniformly, and then repeatedly filtering and dehydrating the sheet. The washing was completed when the electrical conductivity of the filtrate became 100 μS / cm or less.
[0134] In addition, the obtained TEMPO oxidized pulp was analyzed using an X-ray diffraction device, and typical peaks were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0135] Ion-exchanged water was added to the obtained TEMPO oxidized pulp to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose.
[0136] X-ray diffraction confirmed that the fine fibrous cellulose maintained cellulose type I crystals. The fiber width of the fine fibrous cellulose was measured using a transmission electron microscope and found to be 3 to 5 nm. The amount of carboxyl groups measured by the measurement method described below was 0.70 mmol / g.
[0137] <Production Example 11> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the heating time of the chemical-impregnated pulp during phosphorylation was 180 seconds. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described later in [Measurement of amount of phosphorus oxo acid groups] was 0.60 mmol / g.
[0138] <Production Example 12> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the heating time of the chemical-impregnated pulp during phosphorylation was changed to 220 seconds. The amount of phosphoric acid groups (amount of first dissociated acid) measured by the measurement method described later in [Measurement of amount of phosphorus oxo acid groups] was 0.95 mmol / g.
[0139] <Production Example 13> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 9, except that the heating time of the chemical-impregnated pulp during sulfation was changed to 15 minutes. The sulfate group (sulfonic acid group) content measured by the measurement method described later in [Measurement of the amount of sulfur oxoacid groups] was 0.94 mmol / g.
[0140] <Production Example 14> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the solid content concentration during the defibration treatment was 2.4 mass %.
[0141] <Production Example 15> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the solid content concentration during the defibration treatment was 2.9 mass %.
[0142] <Production Example 16> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the solid content during defibration was 4.0% by mass and the number of treatments in the wet-type microparticulation device was one.
[0143] <Production Example 17> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the solid content during defibration was 4.9% by mass and the number of treatments in the wet-type microparticulation device was one.
[0144] <Production Example 18> A fine fibrous cellulose dispersion was obtained in the same manner as in Production Example 1, except that the solid content during defibration was 12.0% by mass and the number of treatments in the wet-type microparticulation device was one.
[0145] <Example 1> (Low thixotropy due to ozone treatment) The ozone concentration was 200 g / m for 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration: 2% by mass, solid content: 20 g). 3 The mixture was stirred for 2 minutes at 25°C in a sealed container and then allowed to stand for 60 minutes. The ozone addition rate was 2.0×10 per 1 g of fine fibrous cellulose. -2 g. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. Thereafter, the mixture was treated three times with a high-pressure homogenizer at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. In this way, the fine fibrous cellulose was made low in thixotropy, and the viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low-thixotropy fine fibrous cellulose dispersion were measured by the methods described below. The fiber width and amount of ionic substituents of the fine fibrous cellulose did not change due to the low-thixotropy treatment. Similarly, in the following examples, the amount of ionic substituents of the fine fibrous cellulose did not change.
[0146] <Example 2> The ozone concentration was 200 g / m for 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration: 2% by mass, solid content: 20 g). 3The mixture was stirred for 2 minutes at 25°C in a sealed container and then allowed to stand for 60 minutes. The ozone addition rate was 2.0×10 per 1 g of fine fibrous cellulose. -2 g. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. In this way, the thixotropy of the fine fibrous cellulose was reduced, and the viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropy fine fibrous cellulose dispersion were measured by the methods described below.
[0147] <Example 3> (Low thixotropy due to ozone treatment) The ozone concentration was 200 g / m for 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration: 2% by mass, solid content: 20 g). 3 The mixture was stirred for 2 minutes at 25°C in a sealed container and then allowed to stand for 30 minutes. The ozone addition rate was 1.0×10 per 1 g of fine fibrous cellulose. -2 g. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. In this way, the thixotropy of the fine fibrous cellulose was reduced, and the viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropy fine fibrous cellulose dispersion were measured by the methods described below.
[0148] <Example 4> Ozone concentration: 40g / m 3 A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except that an ozone / oxygen mixed gas of 2.0×10 was used. The ozone addition rate at this time was 2.0×10 per 1 g of fine fibrous cellulose. -3 The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0149] <Example 5> (Low thixotropy due to enzyme treatment) To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 2% by mass, solid content 20 g), 20 g of an enzyme-containing liquid (AB Enzymes, ECOPULP R, enzyme content approximately 5% by mass) diluted 1000-fold was added, and the mixture was stirred at a temperature of 50° C. for 1 hour. The enzyme addition rate at this time was approximately 5.0×10 per 1 g of fine fibrous cellulose. -5 g. The mixture was then stirred at 100° C. for 1 hour to inactivate the enzyme. The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the resulting low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0150] <Example 6> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 5, except that 4 g of an enzyme-containing liquid (manufactured by AB Enzymes, ECOPULP R, enzyme content approximately 5% by mass) was added by diluting it 1000 times to 1000 g of a fine fibrous cellulose dispersion (solid content concentration 2% by mass, solid content 20 g). The enzyme addition rate at this time was approximately 1.0×10 -5 The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0151] <Example 7> (Low thixotropy due to sodium hypochlorite treatment) To 1000 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 2 mass%, solid content 20 g), 170 g of sodium hypochlorite solution (effective chlorine concentration 12 mass%) was added and stirred at room temperature for 1 hour. The sodium hypochlorite addition rate at this time was 1.02 g per 1 g of fine fibrous cellulose. The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0152] <Example 8> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 7, except that 1.70 g of sodium hypochlorite solution (effective chlorine concentration 12% by mass) was added to 1000 g of fine fibrous cellulose dispersion (solid content concentration 2% by mass, solid content 20 g). The sodium hypochlorite addition rate at this time was 1.02×10 -2 The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0153] <Example 9> (Reducing thixotropy through subcritical water treatment) The fine fibrous cellulose dispersion obtained in Production Example 1 was placed in a reactor, heated to 200°C, and heated for 10 seconds. The pressure in the reactor at this time was 20 MPa. After heating, the reactor was cooled with water, and the low thixotropic fine fibrous cellulose dispersion in the reactor was recovered. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0154] <Example 10> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 9, except that the heating time was set to 1 second. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0155] <Example 11> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 1, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0156] <Example 12> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 2, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0157] <Example 13> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0158] <Example 14> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0159] <Example 15> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 5, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0160] <Example 16> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0161] <Example 17> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 7, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0162] <Example 18> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 8, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0163] <Example 19> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 9, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0164] <Example 20> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 10, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0165] <Example 21> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 2. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0166] <Example 22> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 3. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0167] <Example 23> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 4. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0168] <Example 24> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 7. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0169] <Example 25> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 9. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0170] <Example 26> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except for using the fine fibrous cellulose dispersion obtained in Production Example 10. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0171] <Example 27> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 11. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0172] <Example 28> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 11. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0173] <Example 29> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 8, except for using the fine fibrous cellulose dispersion obtained in Production Example 11. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0174] <Example 30> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 10, except for using the fine fibrous cellulose dispersion obtained in Production Example 11. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0175] <Example 31> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 12. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0176] <Example 32> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 12. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0177] <Example 33> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 8, except for using the fine fibrous cellulose dispersion obtained in Production Example 12. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0178] <Example 34> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 10, except for using the fine fibrous cellulose dispersion obtained in Production Example 12. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0179] <Example 35> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 14. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0180] <Example 36> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 14. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0181] <Example 37> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 8, except for using the fine fibrous cellulose dispersion obtained in Production Example 14. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0182] <Example 38> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 10, except for using the fine fibrous cellulose dispersion obtained in Production Example 14. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0183] <Example 39> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 15. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0184] <Example 40> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 15. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0185] <Example 41> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 8, except for using the fine fibrous cellulose dispersion obtained in Production Example 15. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0186] <Example 42> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 10, except for using the fine fibrous cellulose dispersion obtained in Production Example 15. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0187] <Example 43> The fine fibrous cellulose dispersion obtained in Production Example 16 was used, and the ozone concentration was 40 g / m 3 A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 1, except that an ozone / oxygen mixed gas of 2.0×10 was used. The ozone addition rate at this time was 2.0×10 per 1 g of fine fibrous cellulose. -3 The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0188] <Example 44> The fine fibrous cellulose dispersion obtained in Production Example 17 was used, and the ozone concentration was 40 g / m 3 A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 1, except that an ozone / oxygen mixed gas of 2.0×10 was used. The ozone addition rate at this time was 2.0×10 per 1 g of fine fibrous cellulose. -3 The viscosity, polymerization degree, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0189] <Example 45> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 13. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0190] <Comparative Example 1> For 500 g of the fine fibrous cellulose dispersion obtained in Production Example 1 (solid content concentration 2% by mass, solid content 20 g), an ozone concentration of 200 g / m 3 The mixture was stirred for 2 minutes at 25°C in a sealed container and then allowed to stand for 120 minutes. The ozone addition rate was 4.0×10 per 1 g of fine fibrous cellulose. -2 g. The container was then opened and stirred for 5 hours to volatilize the ozone remaining in the dispersion. The mixture was then treated three times with a high-pressure homogenizer at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion. In this way, the fine fibrous cellulose was made low thixotropic, and the viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0191] <Comparative Example 2> For 100 g of the phosphorylated pulp obtained in Production Example 5 (solid content concentration 20 mass%, solid content 20 g), an ozone concentration of 200 g / m 3 The mixture was stirred for 2 minutes at 25°C in a sealed container and then allowed to stand for 30 minutes. The ozone addition rate was 1.0×10 per 1 g of fine fibrous cellulose. -2 g. The phosphorylated pulp was then washed to remove the remaining ozone. The resulting pulp was then used to prepare a slurry with a solid content of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion containing fine fibrous cellulose. The resulting fine fibrous cellulose dispersion was used as it was to measure the viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze by the methods described below.
[0192] <Comparative Example 3> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Comparative Example 1, except for using the fine fibrous cellulose dispersion obtained in Production Example 6. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0193] <Comparative Example 4> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Comparative Example 2, except for using the phosphorylated pulp obtained in Production Example 8. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0194] <Comparative Example 5> The fine fibrous cellulose dispersion obtained in Production Example 1 was used as it was to measure the viscosity, degree of polymerization, rate of viscosity change, fiber width, fiber length, and haze by the methods described later.
[0195] <Comparative Example 6> The fine fibrous cellulose dispersion obtained in Production Example 6 was used as it was to measure the viscosity, degree of polymerization, rate of viscosity change, fiber width, fiber length and haze by the methods described later.
[0196] <Comparative Example 7> The fine fibrous cellulose dispersion obtained in Production Example 9 was used as it was to measure the viscosity, degree of polymerization, rate of viscosity change, fiber width, fiber length and haze by the methods described later.
[0197] <Comparative Example 8> The fine fibrous cellulose dispersion obtained in Production Example 10 was used as it was to measure the viscosity, degree of polymerization, rate of viscosity change, fiber width, fiber length and haze by the methods described later.
[0198] <Comparative Example 9> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 4, except for using the fine fibrous cellulose dispersion obtained in Production Example 5. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0199] <Comparative Example 10> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 6, except for using the fine fibrous cellulose dispersion obtained in Production Example 5. The viscosity, degree of polymerization, viscosity change rate, fiber width, fiber length, and haze of the obtained low thixotropic fine fibrous cellulose dispersion were measured by the methods described below.
[0200] <Comparative Example 11> A low thixotropic fine fibrous cellulose dispersion was obtained in the same manner as in Example 3, except that the fine fibrous cellulose dispersion obtained in Production Example 18 was used. The low thixotropic fine fibrous cellulose dispersion obtained clearly contained coarse fibers, and had poor haze (haze value at 0.2% concentration) and dispersibility. Therefore, the viscosity, viscosity change rate, and coating suitability of the dispersion, as well as the surface roughness of the coating film and the aggregates of the coating film were not measured or evaluated.
[0201] <Measurement> [Measurement of phosphorus oxoacid group content] The amount of phosphorus oxoacid groups in the fine fibrous cellulose was measured by treating a fibrous cellulose-containing slurry with an ion exchange resin after diluting a fine fibrous cellulose dispersion containing the target fine fibrous cellulose with ion exchange water to a content of 0.2 mass%, and then titrating the slurry with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution every 5 seconds to the fibrous cellulose-containing slurry after the ion exchange resin treatment, while measuring the change in the pH value of the slurry. Nitrogen gas was blown into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the derivative value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the alkali addition is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 1). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated, and this value was taken as the amount of phosphorus oxoacid groups (mmol / g).
[0202] [Measurement of the amount of sulfur oxoacid groups] The amount of sulfate groups was measured by wet ashing of the sample and ICP emission spectrometry. Specifically, the fibrous cellulose-containing slurry obtained in Production Example 7 was completely dried and then weighed, perchloric acid was added, carbonized, and concentrated nitric acid was added to oxidize the carbon to carbon dioxide, to obtain a sample solution consisting only of inorganic substances. This sample solution was diluted at an appropriate ratio and the sulfate ion concentration was measured by ICP emission spectrometry. The amount of sulfur atoms contained in the sample solution was divided by the mass of the weighed fibrous cellulose to obtain the amount of sulfate groups.
[0203] [Measurement of Carboxy Group Amount] The amount of carboxy groups in the fine fibrous cellulose was measured by adding ion exchange water to a fine fibrous cellulose-containing slurry containing the target fine fibrous cellulose to adjust the content to 0.2 mass%, treating the slurry with ion exchange resin, and then titrating the slurry with an alkali. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to a 0.2% by mass slurry containing fine fibrous cellulose, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. In addition, the titration using alkali was performed by measuring the change in the pH value of the slurry while adding 10 μL of 0.1N aqueous sodium hydroxide solution to the fibrous cellulose-containing slurry after the ion exchange resin treatment at 5 seconds. When the change in pH is observed while adding the aqueous sodium hydroxide solution, a titration curve as shown in FIG. 2 is obtained. As shown in FIG. 2, in this neutralization titration, a point is observed where the increment (differential value of pH with respect to the amount of alkali added) is maximum on the curve plotting the measured pH against the amount of alkali added. This maximum point of the increment is called the first end point. Here, the region from the start of the titration to the first end point in FIG. 2 is called the first region. The amount of alkali required in the first region is equal to the amount of carboxyl groups in the slurry used for the titration. The amount of alkali required in the first region of the titration curve (mmol) was divided by the solid content (g) in the fine fibrous cellulose-containing slurry to be titrated to calculate the amount of carboxyl groups introduced (mmol / g). The amount of carboxyl groups introduced (mmol / g) is calculated assuming that the counter ion of the carboxyl group is a hydrogen ion (H + ) (hereinafter referred to as the amount of carboxy groups (acid type)) per gram of mass of fibrous cellulose.
[0204] [Measurement of fiber length and width] The fiber length of the fine fibrous cellulose after the low thixotropy treatment was determined by observing a sample prepared by diluting the fine fibrous cellulose dispersion to 0.001% by mass with an AFM and performing image analysis. The fiber lengths of Examples 1 to 45 were the shortest at 250 nm and the longest at 610 nm, while the fiber lengths of Comparative Examples 1 to 11 were the shortest at 230 nm and the longest at 760 nm. The fiber width of the fine fibrous cellulose after the low thixotropy treatment was determined using an electron microscope. The fiber widths of Examples 1 to 45 and Comparative Examples 1 to 10 were 3 to 5 nm.
[0205] [Measurement of Viscosity of Fine Fibrous Cellulose Dispersion] The viscosity of the fine fibrous cellulose dispersion obtained in the examples and comparative examples was measured as follows. First, the fine fibrous cellulose dispersion was diluted with ion-exchanged water so that the solid content concentration was 0.4% by mass, and then stirred in a disperser at 1500 rpm for 5 minutes. Next, the viscosity of the dispersion thus obtained was measured using a B-type viscometer (manufactured by BLOOKFIELD, analog viscometer T-LVT). The measurement conditions were a rotation speed of 3 rpm, and the viscosity value 3 minutes after the start of the measurement was taken as the viscosity of the dispersion. In addition, the dispersion to be measured was left to stand for 24 hours in an environment of 23°C and relative humidity 50% before the measurement. The liquid temperature of the dispersion during the measurement was 23°C.
[0206] [The viscosity of the dispersion containing fine fibrous cellulose (η β '1, η β Measurement of '2) 1] The fine fibrous cellulose-containing dispersion was measured without dilution using a B-type viscometer (analog viscometer T-LVT manufactured by BLOOKFIELD). The measurement conditions were rotation speeds of 0.3 rpm and 3 rpm, and the viscosity value 3 minutes after the start of measurement was taken as the viscosity of the dispersion. The dispersion to be measured was left to stand for 24 hours in an environment of 23°C and relative humidity 50% before measurement. The liquid temperature of the dispersion during measurement was 23°C. Viscosity at a rotation speed of 0.3 rpm (η β '1) and viscosity at a rotation speed of 3 rpm (η β '2) ratio (0.3 rpm / 3 rpm, η β '1 / η β'2) was calculated as one of the indicators of thixotropy and shown in the table.
[0207] [The viscosity of the original solution of the fine fibrous cellulose dispersion (η α '1, η α Measurement of '2) 2 The fine fibrous cellulose-containing dispersion was measured without dilution using a rheometer (HAAKE, RheoStress1). The measurement conditions were as follows: shear rate 1 sec -1 Viscosity value (η α '1) and 1000sec -1 Viscosity value (η α '2) was taken as the viscosity of the dispersion. The dispersion to be measured was left to stand for 24 hours in an environment of 23°C and relative humidity of 50% before the measurement. The liquid temperature of the dispersion during the measurement was 23°C. Measurement tool: Cone plate (diameter 35 mm, angle 2°) Shear rate: 0.001 to 1000 sec -1 Number of data points: 31 Measurement time: 5 minutes Also, the shear rate is 1 sec -1 Viscosity value (η α '1) and shear rate of 1000 sec -1 Viscosity at (η α '2) (1sec -1 / 1000sec -1 , η α '1 / η α '2) was calculated as one of the indicators of thixotropy and shown in the table.
[0208] [Measurement of specific viscosity and polymerization degree of fine fibrous cellulose] The specific viscosity and degree of polymerization of the fine fibrous cellulose obtained in the examples and comparative examples were measured according to Tappi T230. The cellulose fiber to be measured was dispersed in a dispersion medium to measure the viscosity (referred to as η1), and the blank viscosity (referred to as η0) was measured using only the dispersion medium, and then the specific viscosity (ηsp) and intrinsic viscosity ([η]) were measured according to the following formula. ηsp=(η1 / η0)-1 [η]=ηsp / (c(1+0.28×ηsp)) Here, c in the formula represents the concentration (g / mL) of the fine fibrous cellulose at the time of viscosity measurement. Furthermore, the degree of polymerization (DP) of the fine fibrous cellulose was calculated from the following formula. DP = 1.75 × [η] Since this degree of polymerization is an average degree of polymerization measured by a viscosity method, it is sometimes called the "viscosity average degree of polymerization."
[0209] [Measurement of Viscosity Change Rate of Fine Fibrous Cellulose Dispersion] The viscosity change rate of the fine fibrous cellulose dispersion was measured as follows. (Measurement of viscosity before stirring) First, water and isopropanol were added in order to the fine fibrous cellulose dispersion obtained in the examples and comparative examples so that the viscosity measured by the method described below was about 2500 mPa·s and the mass ratio of water to isopropanol contained in the dispersion was 7:3. The dispersion thus obtained was placed in a cylindrical container with a diameter of 10 cm to a height of 5 cm and stirred at 1500 rpm for 5 minutes with a disperser. One minute after the end of stirring, the viscosity of the obtained fine fibrous cellulose dispersion was measured using a B-type viscometer (manufactured by BLOOKFIELD, analog viscometer T-LVT). The measurement conditions were a rotation speed of 6 rpm, and the viscosity value one minute after the start of measurement was taken as the viscosity of the dispersion. The liquid temperature of the dispersion during the measurement was 23°C. (Stirring with a stirrer) The resulting fine fibrous cellulose dispersion with a viscosity of approximately 2500 mPa s was then poured into a cylindrical container with a diameter of 10 cm to a height of 5 cm, and stirred for 24 hours using an elliptical stirrer with a length of 5 cm, width of 2 cm at the center, and width of 1 cm at the end, while maintaining a 2 cm depression in the center of the liquid surface. The temperature of the dispersion during stirring was 23°C. (Measurement of viscosity after stirring) One minute after the stirring with the stirrer was completed, the viscosity of the fine fibrous cellulose dispersion was immediately measured using a B-type viscometer (BLOOKFIELD analog viscometer T-LVT). The measurement conditions were a rotation speed of 6 rpm, and the viscosity value one minute after the start of the measurement was taken as the viscosity of the dispersion. The temperature of the dispersion during the measurement was 23°C. (Calculation of viscosity change rate) The rate of change in viscosity before and after stirring with a stirrer was calculated using the following formula. Viscosity change rate (%) = (viscosity after stirring - viscosity before stirring) / viscosity before stirring × 100
[0210] [Measurement of haze of fine fibrous cellulose dispersion] The haze of the fine fibrous cellulose dispersion was measured as follows. The fine fibrous cellulose dispersion obtained in the examples and comparative examples was diluted with ion-exchanged water so that the solid content concentration was 0.2% by mass, and then degassed using a planetary centrifugal super mixer (ARE-250, manufactured by Thinky Corporation). The haze of the dispersion thus obtained was then measured with a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) using a glass cell for liquids with an optical path length of 1 cm (MG-40, manufactured by Fujiwara Seisakusho Co., Ltd., reverse optical path) in accordance with JIS K 7136:2000. The zero point measurement was performed with ion-exchanged water placed in the same glass cell.
[0211] [Appearance evaluation of fine fibrous cellulose dispersion] The fine fibrous cellulose dispersions obtained in the Examples and Comparative Examples were subjected to a defoaming treatment using an automatic revolution type super mixer (ARE-250, manufactured by Thinky Corporation). Thereafter, the appearance was visually evaluated according to the following criteria. A: Almost no fibers can be seen with the naked eye and the dispersion liquid is transparent. B: Almost no fibers are visible to the naked eye, and the dispersion is translucent. C: The fibers are not uniformly dispersed and the dispersion is cloudy or granular matter (fiber aggregates) can be seen.
[0212] [Evaluation of defoaming properties of fine fibrous cellulose] The fine fibrous cellulose dispersions obtained in the Examples and Comparative Examples were diluted with ion-exchanged water to a solid content concentration of 1% by mass, then stirred at 4000 rpm for 3 minutes in a disperser, and defoamed using an automatic orbital type super mixer (ARE-250, manufactured by Thinky Corporation). The defoaming ability was evaluated based on the time required to complete the defoaming process, using the following evaluation criteria. A: The defoaming process was completed within 2 minutes. B: The defoaming process was completed within 2 to 4 minutes. C: The defoaming treatment was completed within 4 to 8 minutes. D: The degassing process took longer than 8 minutes to complete.
[0213] [Evaluation of particle dispersibility of fine fibrous cellulose dispersion] The fine fibrous cellulose dispersions obtained in the Examples and Comparative Examples were diluted with ion-exchanged water to a solid content concentration of 1% by mass, and then stirred at 4000 rpm for 3 minutes in a disperser and degassed using an automatic orbital type super mixer (ARE-250, manufactured by Thinky Corporation). 3 The beads were added to the dispersion medium (material: soda glass), and the settling of the beads was confirmed. The particle dispersibility was evaluated according to the following criteria. A: The beads are uniformly dispersed for more than 24 hours. B: The beads are uniformly dispersed for 5 hours or more but less than 24 hours. C: The beads are uniformly dispersed for more than 10 minutes but less than 5 hours. D: Beads settle in less than 10 minutes.
[0214] [Evaluation of paint application suitability] The coating suitability of the paints using the fine fibrous cellulose dispersions obtained in the Examples and Comparative Examples was evaluated as follows. (Preparation of paint containing fine fibrous cellulose) To 100 parts by mass of a fine fibrous cellulose dispersion with a viscosity of approximately 2500 mPa s obtained by the same method as above, 1 part by mass of a lustrous material (aluminum paste WXM7640, manufactured by Toyo Aluminum K.K., aluminum concentration 58-61% by mass) was added, and the mixture was stirred in a disperser at 1500 rpm for 5 minutes to obtain a paint containing fine fibrous cellulose. (Paint circulation and spray coating) The resulting fine fibrous cellulose-containing paint was then circulated in the piping for 24 hours using a pump-type circulation device. Immediately after the end of circulation, the fine fibrous cellulose-containing paint was applied to the wall surface using a spray gun, and the presence or absence of dripping was confirmed. In addition, the presence or absence of settling of the lustrous material in the fine fibrous cellulose-containing paint during application was visually confirmed. Based on the results of dripping of the paint and settling of the lustrous material, the coating suitability of the fine fibrous cellulose-containing paint was evaluated on a four-point scale. A: No dripping or settling of the luster material was observed during coating after the paint was circulated, and the coating suitability was very good. B: Either dripping or settling of the glittering material is observed during coating after paint circulation, but it is minor and the coating suitability is good. C: Dripping and settling of glittering material were observed during coating after paint circulation, and coating suitability was somewhat poor, but there was no problem in practical use. D: There was a lot of dripping and settling of the glittering material during coating after the paint was circulated, making the coating suitability poor and problematic for practical use.
[0215] [Evaluation of Coating Appearance] The appearance of the coating film of the coating material using the fine fibrous cellulose dispersion obtained in this embodiment was evaluated as follows. (Preparation of paint containing fine fibrous cellulose) 24.9g of fine fibrous cellulose dispersion with a solid content concentration of 0.4% by mass was placed in a beaker, and 34.4g of ion-exchanged water, 35.2g of acrylic resin, and 5.49g of hardener were added in that order. The addition was performed while stirring at 1500 rpm with a TK Homo Disper (manufactured by Tokushu Kika Kogyo). After all was added, the mixture was stirred for another 5 minutes, and then degassed with a degassing device (Thinky Corporation, Rotating / Revolving Mixer AR-250). In this way, a fine fibrous cellulose-containing paint with a solid content ratio of acrylic resin 78, hardener 22, and fine fibrous cellulose 0.5 (by mass) was obtained.
[0216] (Preparation of coating film for evaluation) The obtained coating material was applied to a PET (polyethylene terephthalate) film (manufactured by Toray Industries, Inc., product name: Lumirror T60, thickness 75 μm) using an applicator so that the coating thickness after drying would be 30 μm. Immediately after coating, the coating was heated in a dryer at a temperature of 80°C for 30 minutes to obtain a cured coating film using the PET film as the substrate.
[0217] (Surface roughness of coating film) The surface roughness of the resulting cured coating film was measured. Specifically, an optical interference non-contact surface profiler (Ryoka Systems Co., Ltd., non-contact surface / layer cross-sectional profile measuring system VertScan2.0, model: R5500GML) was used to measure the arithmetic mean roughness (Ra (μm)) of the cured coating film over a measurement range of 470.92 μm × 353.16 μm with a ×10 objective lens. Measurements were performed five times per level, and the arithmetic mean roughness was calculated from the average value. Details of the definition, measurement conditions, and calculation method of the arithmetic mean roughness (Ra) were in accordance with JIS B 0601:2013.
[0218] (Number of aggregates) The coating material with a PET film substrate was observed using an optical microscope (Nikon Corporation), and the coating thickness was measured at 1 mm. 2 The number of aggregates with a size of 5 μm or more in the 2 ) was checked at 100 points, and the arithmetic mean value (N / 100) was calculated. The results were evaluated as follows: A: The arithmetic mean value of aggregates with a size of 5 μm or more is 3 pieces / mm2 is less than B: The arithmetic mean value of aggregates with a size of 5 μm or more is 3 pieces / mm 2 or more but less than 8 C: The arithmetic mean value of aggregates with a size of 5 μm or more is 8 pieces / mm 2 More than 13 pieces / mm 2 is less than D: The arithmetic mean value of aggregates with a size of 5 μm or more is 13 pieces / mm 2 That's all. The size of the aggregates was defined as the equivalent circle diameter, and the details of the measurement conditions, calculation methods, etc. were in accordance with JIS Z 8827-1:2008.
[0219] [Table 1]
[0220] [Table 2]
[0221] [Table 3]
[0222] [Table 4]
[0223] [Table 5]
[0224] [Table 6]
[0225] The fibrous cellulose-containing dispersion obtained in the examples had excellent particle dispersibility, and the paint using the dispersion exhibited excellent coating suitability. Furthermore, when the paint using the fine fibrous cellulose-containing dispersion obtained in the examples was used, a coating film with a smooth surface and little generation of aggregates was obtained. Moreover, the fibrous cellulose-containing dispersions obtained in the Examples were excellent in dispersion transparency and also had good defoaming properties.
Claims
1. A fibrous cellulose-containing dispersion comprising: The fibrous cellulose has a fiber width of 1000 nm or less and has an ionic substituent, the amount of the ionic substituent in the fibrous cellulose is 0.10 mmol / g or more and 1.50 mmol / g or less, The degree of polymerization of the fibrous cellulose is 150 or more and 515 or less, The viscosity at 3 rpm using a Brookfield viscometer is 40,000 mPa·s or more and 800,000 mPa·s or less, The concentration of the fibrous cellulose in the dispersion is 1.5% by mass or more and less than 5% by mass. Fibrous cellulose-containing dispersion.
2. The fibrous cellulose-containing dispersion according to claim 1 , wherein the ionic substituent is a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group.
3. 3. The fibrous cellulosic cellulose-containing dispersion according to claim 1, which has a viscosity of 300,000 mPa or more and 5,000,000 mPa or less at 0.3 rpm using a Brookfield viscometer.
4. The fibrous cellulose-containing dispersion according to any one of claims 1 to 3, wherein the ratio of the viscosity at 0.3 rpm using a B-type viscometer to the viscosity at 3 rpm using a B-type viscometer (viscosity at 0.3 rpm / viscosity at 3 rpm) is 5.00 or more and 7.40 or less.
5. Shear rate in rheometer: 1 sec -1 The fibrous cellulose-containing dispersion according to any one of claims 1 to 4, wherein the viscosity under the above condition is 30 Pa·s or more and 400 Pa·s or less.
6. Rheometer shear rate: 1000 sec -1 The fibrous cellulose-containing dispersion according to any one of claims 1 to 5, wherein the viscosity under the above condition is 0.02 Pa·s or more and 1.00 Pa·s or less.
7. Rheometer shear rate: 1000 sec -1 The shear rate in the rheometer is 1 sec. -1 The viscosity ratio under the condition (shear rate 1 sec -1 Viscosity under the condition of shear rate 1000 sec -1 The fibrous cellulose-containing dispersion according to any one of claims 1 to 6, wherein the viscosity (under the condition) of the dispersion is 200 or more and 1,000 or less.
8. The fibrous cellulose-containing dispersion according to any one of claims 1 to 7, wherein the fibrous cellulose-containing dispersion is diluted with a dispersion solvent containing water and isopropol to obtain a dispersion having a mass ratio of water to isopropanol of 7:3 and a viscosity of 2500 mPa·s at 23°C, and when the diluted dispersion is stirred under the following stirring conditions, the viscosity change rate calculated by the following formula is within ±50%; Viscosity change rate (%)=(viscosity after stirring−viscosity before stirring) / viscosity before stirring×100 (Mixing conditions) A dispersion liquid having a viscosity of 2,500 mPa s at 23°C is poured into a cylindrical container having a diameter of 10 cm to a height of 5 cm, and stirred at 23°C for 24 hours using an elliptical stirrer having a length of 5 cm, a width of 2 cm at the center and a width of 1 cm at the end, while maintaining a state in which the center of the liquid surface is recessed by 2 cm.
9. The fibrous cellulose-containing dispersion according to any one of claims 1 to 8, wherein when the fibrous cellulose-containing dispersion is diluted with water to give a dispersion having a fibrous cellulose content of 0.4 mass%, the viscosity of the diluted dispersion at 23°C is 20 mPa·s or more and 4700 mPa·s or less.
10. The fibrous cellulose-containing dispersion according to any one of claims 1 to 9, wherein when the fibrous cellulose-containing dispersion is diluted with water to give an aqueous dispersion having a fibrous cellulose content of 0.2 mass%, the haze of the diluted dispersion is 20% or less.
11. The fibrous cellulose-containing dispersion according to any one of claims 1 to 10, which is for use in a paint.
12. a step of subjecting cellulose fibers having an ionic substituent of 0.10 mmol / g or more and 1.50 mmol / g or less to a defibration treatment to obtain fibrous cellulose having a fiber width of 1000 nm or less; and subjecting the fibrous cellulose to a thixotropic treatment, A method for producing a fibrous cellulose-containing dispersion, wherein the step of subjecting the fibrous cellulose to a thixotropic reduction treatment is a step of reducing the degree of polymerization of the fibrous cellulose to 150 or more and 515 or less.
Citation Information
Patent Citations
Fibrous cellulose-containing dispersion and method for producing same
JP7556323B2
Bright pigment dispersion and method for forming multilayer coating film
WO2017175468A1
Glitter pigment dispersion
WO2018012014A1
